Chemical Compound Chemical Treatment in Animal Husbandry - Xiaoling Tang; Ting Peng (Journal of Chemistry)
The acidulant is widely used in the production of animal husbandry, and its use is affected by many factors, including environmental factors, dosage, diet composition, and animal’s own factors, so only the correct use of the acidulant can bring good results in animal production and financial income. This article takes acidifier as an example to study the application of compound chemical treatment in livestock farms. In this paper, the effect of using acidulant in the first 1 to 3 weeks after early weaning of piglets is obvious through this experimental study. The effect gradually decreases after 3 weeks and basically has no effect after 4 weeks. Experimental studies have found that the combination of organic acids, antibiotics, and high copper is the most effective. These three have different functions and have complementary or additive effects. Under harsh feeding conditions, especially when the environmental sanitation and environmental conditions are relatively poor, the effect of acidulants is better than good feeding conditions. Experimental data show that fulvic acid depletes milk’s somatic cells in a short period of time and then quickly activates immune function, which is indicated by the increase in lymphocytes in the blood. When a large number of somatic cells migrate to the breast, the somatic cells in milk will also increase, thereby improving the immunity mediated by human cells. The experimental results show that the BFA formula added 1% to the cattle feed. After the research control of this experiment, the milk output increased by 9–17%, and the quality milk output increased by 19.12%, so the use of acidulant increased feed compensation and reduces gastrointestinal diseases and the reproduction of microorganisms in the rumen of dairy cows.